Lumbar osteopathic manipulative treatment can improve KOA symptoms: short-term efficacy observation and mechanism analysis - Du, Peiyu; Li, Xi; Yin, Shilin; Li, Wenyi; Sun, Xilong; Zhang, Zekun; Zhao, Jianyong; Shijun, Gao; Du, Shuangqing; Zhang, Di (Frontiers in Bioengineering and Biotechnology, 2024)
Background:Manipulative treatment can effectively improve knee pain and function, but no previous studies have shown that lumbar osteopathic manipulative treatment can improve knee symptoms.To explore the influence of lumbar manipulation on KOA and analyze its principlerelationship between coronal position of lumbar spine and KOA.Methods: Patients were divided into OMT group and DT group according to treatment.WOMAC scores were compared between the two groups, and X-ray examinations before and after treatment were performed in OMT group to analyze the imaging changes.Results: Both OMT group and DT group showed significant improvement in WOMAC score after treatment, and the improvement in OMT group was better than that in DT group. After OMT treatment, cTMI(P=0.034), mL-SOD(P<0.001), mΔL-KOD(P=0.001), LL(P=0.036)and FTA(P=0.026) were significantly changed Conclusion: Compared with drug therapy, lumbar manipulation can better improve WOMAC scores in KOA patients. It relives symptoms by loosening muscles and correcting small joint disorders to improve local knee alignment.